Pengaruh Manajemen Supervisi Dan Profesionalitas Pendidik Dalam Peningkatan Kualitas Pembelajaran PAI di MIN 1 Gresik - Abdullah Zaini (Salimiya: Jurnal Studi Ilmu Keagamaan Islam, 2022)
The existence of educational supervision is very necessary in relation to efforts to stimulate an increase in institutional resources consisting of all school members, namely educators, education staff, and students. The purpose of supervision is so that the quality and quality of learning is always controlled and improved. A supervisor is assigned to organize, facilitate, and help educators to always try to improve quality and become professional teachers. The teacher's professional attitude includes expertise, skills, and proficiency in meeting predetermined standards. Professional educators are able to master the material, choose teaching materials, determine methods, and are able to become motivators for students, as well as have skills and insight that are qualified in the field of education. This paper was compiled to prove the hypothesis regarding the influence of supervisory management and the level of professionalism of educators in an effort to improve the quality of PAI learning.